2009
DOI: 10.1111/j.1524-475x.2008.00451.x
|View full text |Cite
|
Sign up to set email alerts
|

Tissue engineering a model for the human ear: Assessment of size, shape, morphology, and gene expression following seeding of different chondrocytes

Abstract: This study examines the tissue engineering of a human ear model through use of bovine chondrocytes isolated from four different cartilaginous sites (nasoseptal, articular, costal, and auricular) and seeded onto biodegradable poly(l-lactic acid) and poly(L-lactide-epsilon-caprolactone) (50 : 50) polymer ear-shaped scaffolds. After implantation in athymic mice for up to 40 weeks, cell/scaffold constructs were harvested and analyzed in terms of size, shape, histology, and gene expression. Gross morphology reveale… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
81
1
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 101 publications
(87 citation statements)
references
References 40 publications
4
81
1
1
Order By: Relevance
“…2002; Karlsson et al, 2007;Kusuhara et al, 2009;Lohan et al, 2011;Malicev et al, 2009;Naumann et al, 2004;Panossian et al, 2001;Sakaguchi et al, 2005;Seda Tigli et al, 2009;Tay et al, 2004;van Osch et al, 2004;Vinardell et al, 2012;Xu et al, 2004;Yoshimura et al, 2007;Zhang and Spector, 2009). However, precise comparison of the performance of culture-expanded human cells is lacking.…”
Section: The In Vitro and In Vivo Capacity Of Culture-expanded Human mentioning
confidence: 99%
“…2002; Karlsson et al, 2007;Kusuhara et al, 2009;Lohan et al, 2011;Malicev et al, 2009;Naumann et al, 2004;Panossian et al, 2001;Sakaguchi et al, 2005;Seda Tigli et al, 2009;Tay et al, 2004;van Osch et al, 2004;Vinardell et al, 2012;Xu et al, 2004;Yoshimura et al, 2007;Zhang and Spector, 2009). However, precise comparison of the performance of culture-expanded human cells is lacking.…”
Section: The In Vitro and In Vivo Capacity Of Culture-expanded Human mentioning
confidence: 99%
“…Most studies that have used biodegradable scaffold materials have resulted in poor structural integrity (i.e. shape and size stability) of the auricular scaffold after implantation; caused by the short-lived chemical and mechanical stability [27][28][29][30][31]. On the other hand, recent studies that have investigated the use of non-degradable biomaterials for auricular cartilage reconstruction have reported a better structural integrity of the implant [23,25,32] -likely caused by the chemical stability of the support biomaterial, which translates 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 into long-lasting mechanical properties even after implantation.…”
Section: Introductionmentioning
confidence: 99%
“…More experiments should be performed in order to confirm this hypothesis. Elastin is the protein that confers elasticity to elastic cartilage, preventing tissue creeping by stretching under load and recoiling to their original configurations after the load is released (Kusuhara et al, 2009). Immunohistochemical assay showed that an elevated number of auricular chondrocytes from microtia cultured onto CS-PVA-ECH hydrogel were still able to express elastin and type II collagen in concordance with mRNA analysis.…”
Section: Discussionmentioning
confidence: 78%